Abstract 267: A Bibliometric Analysis of Tenecteplase Research Utilizing a Commonly Used Citation Index - Brendan Huang (Stroke: Vascular and Interventional Neurology)
Introduction Tenecteplase is increasingly being used as a first‐line treatment for acute ischemic stroke after several randomized studies demonstrated its safety and efficacy, resulting in a massive increase in the number of published studies on this topic. Our aim was to investigate the most impactful authors and relevant journals that have been instrumental in validating this treatment, in hopes of identifying objective research trends that may assist scientists, health organizations, and funding agencies to collaborate and plan future avenues of research. Methods Using the search terms “Tenecteplase” and “Tenecteplase” AND “Stroke,” 2,683 and 1,150 references were queried, respectively, using the Abstract 20and citation database, Scopus. Scopus Citation Analysis was used to categorize the countries and authors who produced the most research. Metadata was retrieved and transferred to bibliographic visualization software, VOSviewer, for co‐authorship and co‐occurrence analyses to identify trends in tenecteplase research. Results Data visualization software identified three tenecteplase research clusters – myocardial infarction, pulmonary embolism, and acute ischemic stroke. Our bibliographic analysis graphically identified that ischemic stroke currently leads both myocardial infarction and pulmonary embolism in annual publications pertaining to tenecteplase therapy, and further pinpointed perfusion imaging and wake‐up strokes as the most relevant areas of study. The United States led all countries in tenecteplase publications, including exclusively stroke studies. The European Heart Journal led all journals in overall publications, while Stroke led all journals in stroke‐related studies. Conclusion Through the use of bibliographic analysis and data visualization, we identified major articles and journals that reflected and shaped the current landscape of tenecteplase; recognized authors who engaged in tenecteplase research as it progressed from cardiopulmonary disease to stroke; and postulated future avenues of research.